A Study on the Scope of Green Marketing in India: Exploring the Challenges and Opportunities of Green Marketing in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Green marketing is a phenomenon which has developed particular important in the modern market. This concept has enabled for the re-marketing and packaging of existing products which already adhere to such guidelines. Additionally, the development of green marketing has opened the door of opportunity for companies to co-brand their products into separate line, lauding the green-friendliness of some while ignoring that of others. Such marketing techniques will be explained as a direct result of movement in the minds of the consumer market. As a result of this businesses have increased their rate of targeting consumers who are concerned about the environment. These same consumers through their concern are interested in integrating environmental issues into their purchasing decisions through their incorporation into the process and content of the marketing strategy for whatever product may be required. This paper discusses how businesses have increased their rate of targeting green consumers, those who are concerned about the environment and allow it to affect their purchasing decisions. The paper identifies the three particular segments of green consumers and explores the challenges and opportunities businesses have with green marketing. The paper also examines the present trends of green marketing in India and describes the reason why companies are adopting itand future of green marketing and concludes that green marketing is something that will continuously grow in both practice and demand.